Effect of odourised enrichment on pig behaviour – data from part 2 of project ”Smell this" - Vilain Rørvang, Maria; Department of Biosystems and Technology, Swedish University of Agricultural Sciences (Swedish University of Agricultural Sciences, 2026)
This experiment tested whether odorised straw could enhance straw engagement and improve welfare on a commercial farm. It involved 1 600 pigs, from 10 weeks of age to slaughter, housed in pens of approx. 10 littermates. Eighty pens were assigned to one of four treatments: Odorised straw provided in a rack with odour changing 1) weekly or 2) every weekday, or non-odorised straw 3) in a rack or 4) on the floor (empty rack). The remaining 80 pens served as controls (straw provided on the floor, no rack). Odorised treatments were essential oils (lavender, aniseed, ginger, thyme, and pine), and the odourless treatment was mineral oil. Clinical welfare scores (tail damage, ear damage, body soiling) were scored weekly, and behaviour was recorded (weeks 5, 7, and 9). Data collection included straw engagement duration, relative interaction with straw and pen inventory, play (locomotor, social, straw-related), and rubbing and rolling.

Clinical welfare scores
The clinical welfare scores were assessed for all treatment pens and the non-treated pens. This was done by five experienced observers who were not blind to the treatments, or the odours. During the weekly assessments, the experimental staff went through all pig rooms and scored the clinical welfare scores for pigs in both treatment and non-treated pens. All individuals were scored on all three clinical welfare scores: ear damage, tail damage, and body soiling.

Behavioural observations
Behavioural observations were done for all video recorded pens i.e., treatment pens only. All behavioural observations were done by one (straw engagement duration and relative interactions with straw and inventory) or two (play behaviour) experienced observers, who were aware of the experimental procedures but to specific odour/odourless treatment (apart from straw in rack vs on floor).
Due to unforeseen issues with hard drives and the electricity at the farm, some recordings were lost, and the behavioural observations were conducted on the remaining 75% of recordings. Experimental weeks 5, 7, and 9 were chosen for behavioural observations to avoid the beginning (when pigs were acclimatising) as well as the end of the finishing period (to ensure none of the experimental pigs were sent to slaughter), while also ensuring behavioural data spread across the experimental period. Within these weeks, Monday to Friday were chosen for observation i.e., the days where treatments were applied.

Straw engagement duration was an event-based measure. Using the video recordings of the selected pens, the exact time of straw provision was found for each pen. This point in time was used as a starting point when calculating the straw engagement duration per day. The time of straw provision, regardless of whether in rack or on the floor, was noted and the latency until the last pig stopped engaging with straw (i.e., when the pig started doing another behaviour, lying down or drinking) was recorded. Pigs being engaged with the straw was defined as either: ‘engaging with straw in rack’ or ‘engaging with straw on the floor’.

Relative straw and inventory interaction time was a relative time use of resources within the pig pen. This measure was recorded during a fixed focus hour 10:00-11:00 within the normal straw-provision routine. On a few occasions, the chosen pen had not yet received straw (18 out of 298, 1-hour videos), and these were not included in the analysis. Behaviour was extracted from the video recordings, using the ethogram in the affiliated publication. Behaviour sampling was carried out at pen level, and the sum per week of all individuals in a pen performing each of the behaviours was calculated (duration in seconds).

Play behaviour was also observed during the fixed focus hour (10:00-11:00) using the footage. Play behaviour was recorded as frequency and duration of each behaviour using the ethogram (see affiliated publication).

Please see the affiliated publication for the full statistical details, and the readme file for variable descriptions.
For more information about the overarching project please see: https://www.slu.se/en/research/research-catalogue/projekt/l/smell-this---improving-enrichment-materials-for-pigs-using-odours/

Denna studie är en del 2 av ett större projekt som innehåller flera olika delar. Denna specifika studies syfte var att undersöka om dofter kan öka den berikande effekten av halm och om denna effekt uttrycks i grisarnas beteende och välfärd. En mer detaljerade beskrivning finns på den engelska sidan.

Försöken videoövervakades och beteenden blev sedan observerade via videofilmerna.
Data innehåller observerade beteenden för både doft- och kontrollgrupper (dvs. doftberikning och doftlös berikning), samt välfärds värden för samma grupper. En mer detaljerad beskrivning finns på den engelska sidan.
Mer information om det övergripande projektet finns här: https://www.slu.se/forskning/forskningskatalog/projekt/l/lukta-pa-det-har---berikning-av-grisars-miljo-med-hjalp-av-lukter/
Effekten av doftberikning på grisars beteende – data från del 2 av projektet ”Smell this”
Keywords: animal behaviour; animal behaviour; sense organs; animal welfare; swine; svin; olfaction; luktsinne; Sus scrofa; vildsvin; Behavioural Sciences Biology; Etologi; Agricultural and Veterinary sciences; Lantbruksvetenskap och veterinärmedicin; Animal and Dairy Science; Husdjursvetenskap